Estratégias de digitalização comunicacional para micro e pequenas empresas como promotoras da inovação e competitividae em Santarém – PA. - BATISTA, Alessandra Giselle Silva (Universidade Federal do Oeste do Pará, 2024)
Globalization, innovations, and the COVID-19 pandemic promoted changes in negotiations through communication digitalization using digital media. Therefore, Micro and Small Businesses (MSEs) needed to adapt abruptly. To mitigate impacts and generate competitiveness, we transfered Know-how through process mapping, using the Technology-Organization-Environment (TOE) framework, the European Skills Assessment Framework (DIGICOMP), and digital business models. In this sense, we sought to answer the following questions: Q1 - What factors interfere the communication digitalization of MSEs? Q2 - What digital strategies can help increase the competitiveness of MSEs? To this end, bibliographical, documentary, prescriptive research, and action research of a quantitative-qualitative nature were carried out with MSEs in Santarém - Pará. Teaching materials were developed, specifically guides and instructional media programs, to adapt and standardize digital communication processes based on data collection and training. To align the methodology, a pilot was carried out with 11 MPEs and later with 15 MPEs; The results demonstrated that despite the available technology, digital media were not fully utilized by MSEs. The actions promoted sustainable development and increased the competitiveness of the companies served. The main barriers to adapting to digital were the entrepreneurs' time, lack of soft skills (such as leadership and organization), lack of training in digital resources, and generating low employee skills. The influencing factors were flexibility, market pressure, and public policies. It was found that there is room to gain competitiveness by using digital media based on strategic planning development and skills improvement.